Effect of compressive stress on the ferroelectric hysteresis behavior in 0-3 PZT-cement composites - Chaipanich A. (2014)
Lead zirconate titanate (PZT)-cement composites of 0-3 connectivity were produced using 50% PZT vol. content. PZT-cement based composites are developed for use as sensors for smart concrete structures, however, these sensors would in real life be under a certain stress. The effect of stress on the ferroelectric polarization-electric field (P-E) hysteresis of the composites is reported in this present work. It was found that there was a small but noticeable reduction in the remnant polarization (Pir) by ≈ 0.3-0.7 μC/cm2 while the coercive field (Eic) remained approximately the same when the stress was increased from 0 to 57 MPa. © 2009 Elsevier B.V. All rights reserved.